DIGITALIZATION AND TAX REFORM AS A STRATEGY TO INCREASE TAXPAYER COMPLIANCE - Meiliyah Ariani; Abdullah; Watriningsih; Zulhawati (ZILLZELL MEDIA PRIMA, 2025)
This study aims to determine the influence of digitalization, digital services, security, and tax reform on taxpayer compliance in the West Jakarta area. The population in this study consists of taxpayers who are registered with a Taxpayer Identification Number (NPWP) at KPP Jakarta Grogol Petamburan. The sampling method used in this study was accidental sampling, resulting in a total sample of 100 respondents. The data used in this study includes primary and secondary data. Data collection was carried out through a questionnaire in the form of Google Forms and analyzed using SPSS (Statistical Product and Service Solutions) software for Windows, version 25. The results of this study prove that digitalization, digital services, security, and tax reform have a significant influence on the compliance of individual taxpayers in the West Jakarta area. The development of digital-based tax systems, such as e-Filing, e-Billing, and online tax payment services, provides easy access, efficiency, and convenience for taxpayers. The high level of security in the tax system also increases trust and reduces concerns about the risk of data leaks. On the other hand, tax reform that focuses on simplifying procedures and transparency also strengthens taxpayers' trust in the applicable system. With the integration of technology, strengthening regulations, and improving services, the level of taxpayer compliance can continue to increase significantly and sustainably in the future. The implications of this study show that technology optimization, strengthening regulations, and improving the quality of tax digital services are important strategies in increasing taxpayer awareness and compliance in a sustainable manner.